Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1949
DOI: 10.1113/jphysiol.1949.sp004419
|View full text |Cite
|
Sign up to set email alerts
|

A preparation of surviving rat small intestine for the study of absorption

Abstract: Despite the physiological importance of the activities of the intestinal mucosa, there have been few successful attempts to study it in isolation, and the impression has arisen that it is difficult or impossible to set up a satisfactory surviving intestine preparation apart from the body and still with a viable mucosa. The objects of this paper are to show that this is not so, to describe a preparation which can be set up with uniform success, and to describe its major properties.In outline, the preparation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1

Year Published

1953
1953
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(77 citation statements)
references
References 2 publications
4
72
1
Order By: Relevance
“…This finding was consistent with tbat of Fisher and Parsons (1949) who have shown that epithelial cell function becomes disturbed when intestinal segments are exposed to O2 lack for only 20 to 30 sec. Also, McDowell, Wolf and Steer (1955) and Howard and De Feo (1959) have pointed out that ionic shifts between cells and tbe extracellular fluid occur very rapidly after the onset of anoxia.…”
Section: Discussionsupporting
confidence: 92%
“…This finding was consistent with tbat of Fisher and Parsons (1949) who have shown that epithelial cell function becomes disturbed when intestinal segments are exposed to O2 lack for only 20 to 30 sec. Also, McDowell, Wolf and Steer (1955) and Howard and De Feo (1959) have pointed out that ionic shifts between cells and tbe extracellular fluid occur very rapidly after the onset of anoxia.…”
Section: Discussionsupporting
confidence: 92%
“…Procedure for recirculation. The apparatus of Fisher & Parsons (1949) was modified such that a single incubation medium bathed both the mucosal and serosal surfaces of the length of intestine. The operative procedure was similar to that described by Parsons & Volman-Mitchell (1974).…”
Section: Methodsmentioning
confidence: 99%
“…of the same solution, and shaken in flasks as described by Parsons, Smyth & Taylor (1958). As five sacs of intestine were used, and as these could not be made simultaneously, a system had to be devised to eliminate the factor of the order in which the sacs were made, as Fisher & Parsons (1949a) had stressed the importance of minimal delay in setting up in vitro intestinal preparations. The following scheme was used.…”
Section: Methodsmentioning
confidence: 99%
“…Just as this paper is being prepared for press the results of Clarkson & Rothstein (1960) Another result of some interest is the effect of delay in making the sacs, and this seems to be much less than might have been supposed. Fisher & Parsons (1949a) stressed the importance of avoiding any delay in interrupting the oxygen supply of the tissues, and believed the success of the in vitro preparation depended on this. It is clear that with everted sacs the urgency of continuous oxygen supply is much less, and sacs remaining in unoxygenated saline for 24 min at room temperature do not lose their capacity to transport either glucose or water.…”
Section: Effect Of Order Of Making the Sacsmentioning
confidence: 99%